The effects of grafting method and time on the success of grafting in silver linden (Tilia tomentosa Moench.) - Turna, Ahmet Turan; Ayan, Sezgin; Parlak, Salih; Yilmaz, Ergin; Gülseven, Orhan; Akin, Seyma Selin (Turkish Journal of Forestry, 2020)
In this study, it was tried to determine the effect of grafting method and time on the success of graft in silvery linden (Tilia tomentosa Moench.) that is used in urban landscape as well as for therapeutic purposes and is a very important non-wood forest product. The research was carried out from Bursa Forest Nursery affiliated to Bursa Forest Regional Directorate. It was used the methods of cleft scion graft and chip budding graft which applied during March and September with 20-day interval. As a result of the research; The grafting in March, the highest success rate was found in 57% in the method of cleft scion grafts and %29 in the method of chip budding grafts. The grafting success in April was %14 by using the method of cleft scion graft. High temperatures occurring during the summer season were considered as the main reasons for the inability to be successful in grafts.
Keywords: tilia; Mühendislik; Forestry; kallus; chip budding graft; SD1-669.5; Ihlamur; Aşı; Aşı tutma; Yarma kalem aşı; Yongalı göz aşı; Kallus; aşı tutma; aşı; cleft scion graft; Engineering; grafting success; yongalı göz aşı; ihlamur; graft; callus; Tilia; Graft; Grafting success; Cleft scion graft; Chip budding graft; Callus; yarma kalem aşı; 15. Life on land